Pemanfaatan Jejaring Sosial dalam Mencari Referensi Resep Makanan Pendamping ASI bagi Working Mom - Kurnia, Ari; Asiah, Nurul; Cempaka, Laras; Pujadi Susilo, Tri (Indonesian Journal for Social Responsibility, 2020)
The babies are six months and over enter the fulfillment phase of complementary food. Working Mom often has difficulty in preparing the child's food, due to limited time and knowledge of food recipes, so using frozen food is an easy way to provide food. Apart from being considered more economical, cleanliness is also more guaranteed, and the most important thing is that nutrition is fulfilled and fresh when consumed even though you have to struggle with time. The purpose of this Community Service is to educate working mom in utilizing social media as a means of finding information, as well as a verified, trusted source. The method used was a Focus Group Discussion (FGD) with approximately 30 participants from the Mom Blogger Community and the City of Pelangi in Pancoran, South Jakarta. The FGD’s result, the Working Mom utilizes social media because of their network and the ease of making food, no longer looking for trusted sources because of their lack of understanding in using smartphones, so that even though the making of MPASI recipes is accessed through a number of mass media and social media, it is necessary to consider, composition, material handling, processing techniques, sanitation and storage techniques.